2015
DOI: 10.1007/s00702-015-1387-3
|View full text |Cite
|
Sign up to set email alerts
|

1H- and 13C-NMR spectroscopy of Thy-1-APPSL mice brain extracts indicates metabolic changes in Alzheimer’s disease

Abstract: Biochemical alterations underlying the symptoms and pathomechanisms of Alzheimer's disease (AD) are not fully understood. However, alterations of glucose metabolism and mitochondrial dysfunction certainly play an important role. (1)H- and (13)C-NMR spectroscopy exhibits promising results in providing information about those alterations in vivo in patients and animals, especially regarding the mitochondrial tricarboxylic acid (TCA) cycle. Accordingly, transgenic mice expressing mutant human amyloid precursor pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…1 H-[ 13 C]-NMR spectroscopy analyses of the APP swe -PS1dE9 mouse model of AD showed a decrease in glutamate, GABA, and glutamine, which suggested an impaired glutamatergic and GABAergic glucose oxidation and neurotransmitter cycle in these mouse brains [78]. 1 H- 13 C spectroscopy analyses of Thy-1-APPSL model, expressing mutant human APP, suggested that mitochondrial dysfunction may contributed to the glutamine synthetase impairment and increased metabolism of glutamate via the GABA shunt [79]. Glucose metabolism was clearly reduced by ~50% in a 3xTG-AD model as exhibited by the decreased levels of metabolites derived from the TCA cycle (glutamate, glutamine, GABA, and NAA) [80].…”
Section: Energy Metabolism In Brain Aging and Alzheimer’s Diseasementioning
confidence: 99%
“…1 H-[ 13 C]-NMR spectroscopy analyses of the APP swe -PS1dE9 mouse model of AD showed a decrease in glutamate, GABA, and glutamine, which suggested an impaired glutamatergic and GABAergic glucose oxidation and neurotransmitter cycle in these mouse brains [78]. 1 H- 13 C spectroscopy analyses of Thy-1-APPSL model, expressing mutant human APP, suggested that mitochondrial dysfunction may contributed to the glutamine synthetase impairment and increased metabolism of glutamate via the GABA shunt [79]. Glucose metabolism was clearly reduced by ~50% in a 3xTG-AD model as exhibited by the decreased levels of metabolites derived from the TCA cycle (glutamate, glutamine, GABA, and NAA) [80].…”
Section: Energy Metabolism In Brain Aging and Alzheimer’s Diseasementioning
confidence: 99%
“…We recently demonstrated that MH84 improved mitochondrial dysfunction in a cellular model of AD [ 36 ]. In the present study, we extended the pharmacological characterization of MH84 to 3-month-old Thy-1 AβPP SL mice which are characterized by enhanced AβPP processing and cerebral mitochondrial dysfunction, representing a mouse model of early AD [ 37 , 38 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…This led to a decrease in the flux of glucose being converted into TCA cycle metabolites, a process critical to generating neurotransmitters and maintaining synaptic plasticity. In fact, metabolic alterations in these mitochondrial TCA cycle metabolites have been demonstrated in different rodent models of Alzheimer's disease (Dedeoglu et al 2004;Marjanska et al 2005;Salek et al 2010;Esteras et al 2012;Tiwari & Patel, 2012;Haris et al 2013;Nilsen et al 2013;van Duijn et al 2013;Doert et al 2015) and clinical cases (Lin et al 2003). These studies suggest that both lowered brain glucose uptake and alternations in mitochondrial TCA cycle function contribute to the hypometabolic state observed in ageing and Alzheimer's disease.…”
mentioning
confidence: 99%